PELATIHAN PENERAPAN 8 TEKNIK PERMAINAN INTERAKTIF DALAM PEMBELAJARAN BAHASA INGGRIS, PERANCIS, JERMAN, DAN JEPANG: The Training of the Application of 8 Interactive Game Techniques in English, French, German, and Japanese Language Learning - Satiakemala, Silvi; Dian Agustina; Happita, Okky Dwi (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2024)
Abstract: This community service activity aimed to provide training to high school teachers on the application of eight interactive game techniques in foreign language classrooms. The methods used in this community service program were lectures and demonstrations. The games introduced included Whispering Game, Chair Game, Mime Game, Tap It! Game, Throw the Ball Game, Word Order Game, Speak Now! Game, and Tongue Twister. These game techniques were designed to be implemented in foreign language teaching, particularly in English, French, German, and Japanese classes, which are the foreign languages taught at STBA YAPARI. The teachers participating in this training came from various language teaching backgrounds, such as English, French, German, and Japanese. Through this training, participants learned how to use these games in classroom activities to create a more engaging and interactive learning environment, showing the relevance of these game techniques to foreign language teaching. After attending the training, the teachers felt more confident in applying innovative teaching methods in their respective language classes. This activity successfully equipped the teachers with practical skills to enhance student engagement and improve the overall learning experience in foreign language education. Keywords: Training; Community Service; Game Techniques; Teaching   Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pelatihan kepada guru-guru SMA tentang penerapan delapan teknik permainan interaktif dalam kelas bahasa asing. Metode yang dilakukan pada kegiatan PkM ini adalah ceramah dan demonstrasi, Permainan yang diperkenalkan antara lain Whispering Game, Chair Game, Mime Game, Tap It! Game, Throw the Ball Game, Word Order Game, Speak Now! Game, dan Tongue Twister. Teknik-teknik permainan ini dirancang untuk dapat diterapkan dalam pengajaran bahasa asing, khususnya dalam kelas bahasa Inggris, Prancis, Jerman, dan Jepang, yang merupakan bahasa-bahasa asing yang diajarkan di STBA YAPARI. Guru-guru yang mengikuti pelatihan ini berasal dari berbagai latar belakang pengajaran bahasa, seperti bahasa Inggris, Prancis, Jerman, dan Jepang. Melalui pelatihan ini, hasilnya adalah peserta mempelajari cara menggunakan permainan-permainan tersebut dalam kegiatan pembelajaran di kelas untuk menciptakan suasana belajar yang lebih menarik dan interaktif adanya relevansi antara teknik permainan dengan pengajaran bahasa asing. Setelah mengikuti pelatihan, para guru merasa lebih percaya diri dalam menerapkan inovasi metode pengajaran di kelas bahasa mereka masing-masing. Kegiatan ini berhasil memberikan para guru keterampilan praktis untuk meningkatkan keterlibatan siswa dan memperbaiki pengalaman belajar secara keseluruhan dalam pengajaran bahasa asing. Kata Kunci: Pelatihan; Pengabdian kepada Masyarakat; Teknik Permainan; Pengajaran